1998
DOI: 10.1037/0022-3514.75.2.374
|View full text |Cite
|
Sign up to set email alerts
|

Partner verification: Restoring shattered images of our intimates.

Abstract: When spouses received feedback that disconfirmed their impressions of their partners, they attempted to undermine that feedback during subsequent interactions with these partners. Such partner verification activities occurred whether partners construed the feedback as overly favorable or overly unfavorable. Furthermore, because spouses tended to see their partners as their partners saw themselves, their efforts to restore their impressions of partners often worked hand-in-hand with partners' efforts to verify … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
98
0
2

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(103 citation statements)
references
References 35 publications
(47 reference statements)
3
98
0
2
Order By: Relevance
“…McLean and Pasupathi (in press) found that between newly dating romantic partners reasoning that centers on self-stability is more common and adaptive than reasoning focused on self-change, perhaps by diminishing uncertainty about who we are with close others (e.g., De La Ronde, & Swann, 1998). Similarly, there is also a risk in sharing vulnerable stories, to which some audiences are uncomfortable responding , as well as risks to elaborative narration that come with distracted listeners (Pasupathi & Hoyt, NEW DIRECTIONS FOR CHILD AND ADOLESCENT DEVELOPMENT • DOI: 10.1002/cd 2009).…”
Section: Contexts: When Should We (Not) Reasonmentioning
confidence: 97%
“…McLean and Pasupathi (in press) found that between newly dating romantic partners reasoning that centers on self-stability is more common and adaptive than reasoning focused on self-change, perhaps by diminishing uncertainty about who we are with close others (e.g., De La Ronde, & Swann, 1998). Similarly, there is also a risk in sharing vulnerable stories, to which some audiences are uncomfortable responding , as well as risks to elaborative narration that come with distracted listeners (Pasupathi & Hoyt, NEW DIRECTIONS FOR CHILD AND ADOLESCENT DEVELOPMENT • DOI: 10.1002/cd 2009).…”
Section: Contexts: When Should We (Not) Reasonmentioning
confidence: 97%
“…In many cases, Wrst impressions turn into lasting ones, through a mix of initial accuracy, information-processing biases, and/or self-fulWlling prophecies (De La Ronde & Swann, 1998;Kunda, 1999;Murray, Holmes, & GriYn, 1996). Nevertheless, it is also common for impressions to change over the course of acquaintanceship, at times demonstrating dramatic reversals (Felmlee, 2001;Paulhus, 1998;Ybarra, 2001).…”
mentioning
confidence: 93%
“…According to self-verification theory (De La Ronde & Swann, 1998;Swann et al, 1994), individuals are more satisfied in relationships in which their partners' views confirm their views of themselves. Thus, individuals should be less satisfied when their partners' views are incongruent with self-views, whether such views are overly negative (derogation) or overly positive (enhancement).…”
Section: Self-verification Versus Positive Illusionsmentioning
confidence: 99%